SOIL AND LEAF WATER POTENTIAL OF QUERCUS SEMECARPIFOLIA AT PHULCHOWKI HILL, NEPAL - Poudyal, K. (Ecoprint: An International Journal of Ecology, 2014)
Quercus semecarpifolia is a high altitude oak and dominant species of central Himalayan vegetation.In the central Himalaya, plants are subjected to a prolonged dry period, thus developing moisturestress. Soil water potential at 15 cm and 30 cm depth, predawn and midday leaf water potential andtheir relationship with stomatal conductance and phenological behaviour was studied at PhulchowkiHill, Kathmandu to evaluate the drought adaptation strategy of Q. semecarpifolia in a pure stand at2130 m elevation. The natural ecosystem of Himalayan region has a characteristic climatic pattern ofconcentrated rainfall and a prolonged dry season which have a strong effect on the adaptability of thisspecies. It maintained a high predawn leaf water potential (ΨL pd) and stomatal conductance (gw)despite low soil water Ψ and ΨL pd . Lowest Ψs and ΨL pd were observed in March 1999, when therewas almost no rain for five months. Mean ΨL pd and ΨL md were (–1.79 and –2.29 MPa, respectively).Patterns of ΨL pd and ΨL md correlated significantly with soil Ψ, and phenology as ΨL pd oftenincreased during leafing but not with gw. DOI: http://dx.doi.org/10.3126/eco.v20i0.11473 ECOPRINT An International Journal of Ecology Vol. 20, 2013 page: 115-121